PENGATURAN PENYELENGGARAAN PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2024 BERDASARKAN UNDANG-UNDANG NOMOR 10 TAHUN 2016 - Kartika Nabela, Tiara; Arfa'i, Arfa'i (Universitas Jambi, Fakultas Hukum, 2023)
Based on Law Number 10 of2016 article 201 paragraph 8 determines simultaneousnational voting in the election of governors and deputy governors, regents and deputyregents, as well as mayors and deputy mayors throughout the territory of the Unitary Stateof the Republic of Indonesia to be held in November 2024. This research aims: 1). To findout and analyze the implementation of the implementation of simultaneous regional headelections in 2024 in Indonesia. 2). To find out and analyze the supervision of simultaneousregional head elections in 2024. The research method used in this study is a normative juridical method. This study usesastatutory,historicalandconceptualapproach.Presidential elections (Pilpres), legislative elections (Pileg) and regional head elections(Pilkada)wereheldinthesameyear.RegardingtheimplementationofPilkadaasstipulatedin Article 18 paragraph (4) of the 1945 Constitution, regional election is a regionalgovernment election regime and not an election regime as referred to in Article 22E of the1945 Constitution. The 2024 elections and regional elections will be very complex becausethe stages of holding elections will take place in parallel with the stages of holding theregionalelections.Forthisreason,effortstoimprovetheprocessofholdingelectionsinthefuture areneeded. Â